Visualisasi Matriks Biofilm Eschericia coli dengan Media Bacteriological Peptone, Sucrose dan Ethanol - Dwi Marlina; Mala Kurniati; Fauzan Hamid; Fivi Larasathi; Febtri Irnawita (Jurnal Kesehatan, 2018)
Escherichia coli is a bacterium which is found in the intestines as a normal flora. In 2011, WHO (World Health Organization) showed that 14% of Children's Deaths that is caused by Escherichia coli. On the other hand, Escherichia colicauses 30-40% incidence of Nosocomial Urinary Tract Infection was associated with the use of urinary catheters. In extreme conditions, Escherichia coli can create biofilms, such as at reduced nutrient conditions, pH 7-7, and temperature 200C - 400C. Biofilm is formed from Escherichia coli that is contained EPS (extracellular polymeric substances). It has function as protector of bacterial cells. EPS contains glucuronic acid and Manosa. The formation of Biofilm can extend treatment process of patients and can cause chronic and recurrent inflammatory process. Aims this study is to know the characteristics of Escherichia coli biofilm and visualize the biofilm produced using sucrose 2%, 5% ethanol and 25% Peptone bacteriological in a culturing process. This study is an experimental and use microorganisms Escherichia coli which is cultured in  Laboratory of Microbiology, University of Lampung and used Scanning Electron Microscope (SEM) for visualization and Aurum (Au) for coating. Based on the findings of observation under SEM (Scanning Electron Microscope), Escherichia coli has a thick layer as a biofilm, particularly in Bacteriological Peptone 25%.  Therefore, bacterial cell colonies sheltered perfect from various antibacterial. Conclusion: Escherichia coli perfectly can create biofilms. For advanced research, can find the inhibitor of biofilm and destroyer of Escherichia coli cells.